2007
DOI: 10.1002/cbf.1456
|View full text |Cite
|
Sign up to set email alerts
|

The effect of NQO1 polymorphism on the inflammatory response in cardiopulmonary bypass

Abstract: Cardiopulmonary bypass (CPB) has been associated with systemic inflammatory response syndrome (SIRS). Endothelial dysfunction related to non-laminar flow during CPB is known to play a key role in this complex pathology. Antioxidant response element (ARE) dependent NAD(P)H:quinone oxidoreductase 1 (NQO1) promoter is a regulatory element involved in the anti-inflammatory mechanism in vasculature exposed to non-laminar flow. Mutation of the NQO1 could represent a novel anti-inflammatory effect in CPB. The goal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Vascular endothelium from subjects with the CC genotype show NQO1 enzymatic activity by immunostaining, whereas subjects with the CT genotype show decreased activity and those with the TT genotype show no activity [8]. Furthermore, a recent report demonstrates an association between NQO1 polymorphism and the inflammatory response in cardiopulmonary bypass [18]. In that study, although there was a limited patient population, interleukin-6 secretion was higher and non-laminar flow was more deleterious in T allele carriers than in patients with the CC genotype during cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 98%
“…Vascular endothelium from subjects with the CC genotype show NQO1 enzymatic activity by immunostaining, whereas subjects with the CT genotype show decreased activity and those with the TT genotype show no activity [8]. Furthermore, a recent report demonstrates an association between NQO1 polymorphism and the inflammatory response in cardiopulmonary bypass [18]. In that study, although there was a limited patient population, interleukin-6 secretion was higher and non-laminar flow was more deleterious in T allele carriers than in patients with the CC genotype during cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 98%
“…A recent epidemiological study involving 834 patients with type 2 diabetes demonstrated that patients with NQO1*2 polymorphism exhibited a higher prevalence of atherosclerotic plaques of carotid artery than those without this polymorphism [33]. Another study in patients undergoing standard coronary artery bypass grafting showed a greater inflammatory response, as revealed by increased serum interleukin-6 levels, in the subjects with NQO1*2 genotype as compared with the patients without this polymorphism [34]. Significantly higher levels of C-reactive protein, a biomarker for coronary heart disease, were reported to occur in coronary heart disease patients with lower NQO1 activity [35], indicating a protective role for NQO1 in cardiovascular inflammation.…”
Section: Role Of Nqo1 In Human Cardiovascular Diseases and Related Comentioning
confidence: 94%
“…The second cluster contains genes that have been associated with the anti-inflammatory responses (Arg1, Spp1, Nqo1, Met, Il1rn, Slc7a2, Nt5e, Chst11, and Pdpn). [39][40][41][42][43][44][45][46][47] These gene were expressed at low levels on the unmodified PDMS surfaces. The opposite response was observed for the expression of these gene clusters on the Z2-Y12 modified surfaces.…”
Section: Lipids Directly Modulate the Transcriptome Of Macrophages Ex...mentioning
confidence: 99%